Republic of Madagascar : Second Review Under the Extended Credit Facility Arrangement and Request for Modification of Performance Criteria-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2017)
This paper discusses Madagascar's Second Review Under the Extended Credit Facility (ECF) Arrangement and Request for Modification of Performance Criteria (PC). Madagascar's implementation of its economic program supported by the ECF has remained strong. All quantitative PCs and indicative targets were met at end-June 2017, and the program's structural agenda is also advancing. The gradual economic recovery has continued, with solid growth and continued macroeconomic stability despite the drought and cyclone that affected Madagascar in early 2017. Fiscal performance has been roughly as planned, with strong revenue performance offsetting some unexpected spending pressures in 2017.